Anti-Inflammatory Effects of Metabolites from Antarctic Fungal Strain Pleosporales sp. SF-7343 in HaCaT Human Keratinocytes - Linsha Dong; Hye Jin Kim; Thao Quyen Cao; Zhiming Liu; Hwan Lee; Wonmin Ko; Youn-Chul Kim; Jae Hak Sohn; Tai Kyoung Kim; Joung Han Yim; Dong-Sung Lee; Hyuncheol Oh (International Journal of Molecular Sciences, 2021)
Chemical investigation of the Antarctic fungi Pleosporales sp. SF-7343 revealed four known secondary fungal metabolites: alternate C (1), altenusin (2), alternariol (3), and altenuene (4). The compound structures were identified primarily by NMR and MS analyses. Atopic dermatitis, an inflammatory disease, is driven by the abnormal activation of T helper (Th) 2 cells and barrier dysfunction. We attempted to identify the anti-inflammatory components of SF-7343. Initial screening showed that compounds 1 and 3 inhibited the secretion of interleukin-8 and -6 in tumor necrosis factor-α/interferon-γ-treated HaCaT cells, and these compounds also showed inhibitory effects on CCL5 and CCL22. Compounds 1 and 3 also downregulated the protein expression levels of intercellular adhesion molecule-1 and upregulated the expression of filaggrin and involcurin. The mechanism study results showed that compounds 1 and 3 inhibited nuclear translocation of nuclear factor-kappa B p65 and the phosphorylation of STAT1 and STAT3. Compound 1, but not compound 3, significantly promoted the expression of heme oxygenase (HO)-1. The effects of compound 1 were partly reversed by co-treatment with a HO-1 inhibitor, tin protoporphyrin IX. Taken together, this study demonstrates the potential value of Antarctic fungal strain SF-7343 isolates as a bioresource for bioactive compounds to prevent skin inflammation.